Factors affecting users' mobile technology usage intentions: an example of QR code scanning for mobile commerce. (2017) - Ho, Chien-Ta Bruce; Yang, Jhong-Min Denis
Mobile commerce is supported by mobile technologies called applications (apps) installed on mobile devices. This study uses QR code, one of the most compelling apps for mobile commerce, as research context example attempts to explore factors that affecting users' mobile technology usage intentions. We use the theory of reasoned action (TRA) as a research framework. Structural equation modelling analysis was conducted using SmartPLS 3.0 with 172 samples. All of the hypotheses are supported by significant path coefficients and high levels of R². While this appears to be a perfect result, it does not explain phenomena that the authors observed during sampling procedures and could not by itself solve the problems that marketers face in their promotion of mobile QR code usage. Therefore, the study was extended through qualitative analysis. We determined that there are four reasons that individuals cannot scan QR codes and six factors in limited usage, which explain customers' scanning willingness and are crucial to future practice. Finally, this paper discusses practical and academic implications and recommendations based on these findings.